Engineering AvidCARs for combinatorial antigen recognition and reversible control of CAR function - Benjamin Salzer (Nature Communications, 2020)
The lack of tumour-specific antigens and control over T-cell activity limits the development of CAR-T cell therapies for solid tumours. Here the authors present an avidity-controlled CAR platform with inducible logic control functions.